Podocyte senescence: from molecular mechanisms to therapeutics - Qian Zhao; Yongzhang Huang; Ningying Fu; Caixia Cui; Xuan Peng; Haiyan Kang; Jie Xiao; Guibao Ke (Renal Failure)
As an important component of the glomerular filtration membrane, the state of the podocytes is closely related to kidney function, they are also key cells involved in aging and play a central role in the damage caused by renal aging. Therefore, understanding the aging process of podocytes will allow us to understand their susceptibility to injury and identify targeted protective mechanisms. In fact, the process of physiological aging itself can induce podocyte senescence. Pathological stresses, such as oxidative stress, mitochondrial damage, secretion of senescence-associated secretory phenotype, reduced autophagy, oncogene activation, altered transcription factors, DNA damage response, and other factors, play a crucial role in inducing premature senescence and accelerating aging. Senescence-associated-β-galactosidase (SA-β-gal) is a marker of aging, and β-hydroxybutyric acid treatment can reduce SA-β-gal activity to alleviate cellular senescence and damage. In addition, CCAAT/enhancer-binding protein-α, transforming growth factor-β signaling, glycogen synthase kinase-3β, cycle-dependent kinase, programmed cell death protein 1, and plasminogen activator inhibitor-1 are closely related to aging. The absence or elevation of these factors can affect aging through different mechanisms. Podocyte injury is not an independent process, and injured podocytes interact with the surrounding epithelial cells or other kidney cells to mediate the injury or loss of podocytes. In this review, we discuss the manifestations, molecular mechanisms, biomarkers, and therapeutic drugs for podocyte senescence. We included elamipretide, lithium, calorie restriction, rapamycin; and emerging treatment strategies, such as gene and immune therapies. More importantly, we summarize how podocyte interact with other kidney cells.